The superconducting properties of MgB2 synthesized by reaction of Mg and higher boride phase - Tan, Kim Lee; Tan, Kwee Yong; Chen, Soo Kien; Shaari, Abdul Halim; Lim, Kean Pah (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
In this work, the synthesis of MgB2 by reaction between MgB4 and Mg has been investigated. The MgB4 powders were initially acid-washed in order to eliminate mainly as well as other impurities. Later, an appropriate amount of Mg was added for reaction at temperature range from 650°C to 950°C for 4 hours. The samples were characterized by x-ray diffraction (XRD), scanning electron microscope (SEM) and SQUID magnetometer (MPMS). Results from XRD showed the dominant phase of MgB2 with some impurities of MgB4 and MgO in all samples. The scanning electron micrographs showed denser microstructures compared to samples obtained by direct in-situ reaction of Mg and B. However, the measured physical density was decreased upon increasing the sintering temperature attributed to the loss of Mg. The superconducting transition temperature, Tc at 37.2K was found to improve at lower sintering temperature.